Effect of Massachusetts healthcare reform on racial and ethnic disparities in admissions to hospital for ambulatory care sensitive conditions: retrospective analysis of hospital episode statistics - McCormick, Danny (BMJ, 2015)
Objectives To examine the impact of Massachusetts healthcare reform on changes in rates of admission to hospital for ambulatory care sensitive conditions (ACSCs), which are potentially preventable with good access to outpatient medical care, and racial and ethnic disparities in such rates, using complete inpatient discharge data (hospital episode statistics) from Massachusetts and three control states. Design Difference in differences analysis to identify the change, overall and according to race/ethnicity, adjusted for secular changes unrelated to reform. Setting Hospitals in Massachusetts, New York, New Jersey, and Pennsylvania, United States. Participants Adults aged 18-64 (those most likely to have been affected by the reform) admitted for any of 12 ACSCs in the 21 months before and after the period during which reform was implemented (July 2006 to December 2007). Main outcome measures Admission rates for a composite of all 12 ACSCs, and subgroup composites of acute and chronic ACSCs. Results After adjustment for potential confounders, including age, race and ethnicity, sex, and county income, unemployment rate and physician supply, we found no evidence of a change in the admission rate for overall composite ACSC (1.2%, 95% confidence interval −1.6% to 4.1%) or for subgroup composites of acute and chronic ACSCs. Nor did we find a change in disparities in admission rates between black and white people (−1.9%, −8.5% to 5.1%) or white and Hispanic people (2.0%, −7.5% to 12.4%) for overall composite ACSC that existed in Massachusetts before reform. In analyses limited to Massachusetts only, we found no evidence of a change in admission rate for overall composite ACSC between counties with higher and lower rates of uninsurance at baseline (1.4%, −2.3% to 5.3%). Conclusions Massachusetts reform was not associated with significantly lower overall or racial and ethnic disparities in rates of admission to hospital for ACSCs. In the US, and Massachusetts in particular, additional efforts might be needed to improve access to outpatient care and reduce preventable admissions.